Rekayasa Arsitektur Buku Tamu Digital - Purwatiningtyas, P; Rani, R.P.S.; Listiyono, Hersatoto; Mulyani, Sri (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The guest book is a means that can be used to find out how many guests have come to a place or other uses that require data from visitors to find out about service activities in an institution. Currently there are still many office agencies that use manual or handwritten methods. into the book to record the guest list before entering the office area. Then the book will be stored in the guard post. This is of course considered less effective because it will pose various risks. To anticipate the risks that will occur, a web-based digital guest book is created that can change the use of paper guest books. This guest book was created using the programming language HTML, PHP and the Bootstrap framework and created using the Waterfall method. Guest data will be saved automatically into the database that has been provided and can be processed by the admin. The final result of this research is a digital guest book that can make it easier for officers to store archives, process data, and print data when needed.